Strategy or symptom: Semantic clustering and risk of Alzheimer's disease-related impairment. Issue 8 (13th September 2020) - Ford, Jamie; Zheng, Bang; Hurtado, Barbara; de Jager, Celeste A.; Udeh-Momoh, Chi; Middleton, Lefkos; Price, Geraint
ABSTRACT: Alzheimer's disease (AD) is the most common form of dementia, impacting global cognitive performance, including episodic memory. Semantic clustering is a learning strategy involving grouping words of similar meaning and can improve episodic memory performance, e.g., list learning. As the APOE ε4 allele is the most validated genetic risk factor for AD, we predicted that its presence would be associated with poorer list learning performance, and we hypothesized that semantic clustering moderates or mediates this association. The sample comprised 699 healthy older adults participating in the CHARIOT PRO Main Study, 169 of whom were APOE ε4 carriers. Participants' ability to form groups of related stimuli (assessed via a categorization task, CAT), and their use of semantic clustering during list learning, were investigated using the Neuropsychological Assessment Battery (NAB). CAT scores predicted the use of semantic clustering in, and performance on, the list learning task. CAT scores were not significantly lower in APOE ε4 carriers, suggesting that the ability to categorize was preserved. However, APOE ε4 carriers made less use of semantic clustering in list learning. Semantic clustering use partially mediated the relationship between CAT scores and list learning performance, and, in women only, moderated the impact of APOE ε4 on list learning performance. The results suggest that better categorization ability is associated with greater use of mnemonic strategies and better performance on memory tasks regardless of genetic risk, but that APOE ε4 carriers make less use of such strategies. Furthermore, female APOE ε4 carriers may benefit more than their non-carriers from using semantic clustering to aid list learning. Thus, semantic clustering may be a contributing factor of their "cognitive reserve", compensating for potential deficits in episodic memory.